Schwann cell TRPA1 mediates neuroinflammation that sustains macrophage-dependent neuropathic pain in mice - Francesco De Logu (Nature Portfolio, 2017)
Following peripheral nerve injury, influx of immune cells to the site may contribute to the development of chronic pain. Here the authors show that TRPA1 is expressed on Schwann cells and contributes to immune cell influx in a mouse model of neuropathic pain.